The Teacher's Problems in Implementing Curriculum 2013 at State Senior High School 3 of West Halmahera - Suhaimi Tegamuni; Kristin Natalia Ugu (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
This research attempted to figure out the problems that teachers in senior high schools dealt with in implementing Curriculum 2013 and what efforts they had taken to overcome the problems. By employing descriptive qualitative method, the researcher took data by distributing questionnaire and by observing the classroom processes. Two senior high school teachers were involved as the participants. They were English teachers in the Senior High School 3 on West Halmahera. From the analysis of the data, it has been found that some problems regarding to the improvement of the students’ academic improvement and some efforts to overcome the problems were discussed.